Senior high school and the labor market perspectives of grade 12 students and human resource officers - Orbeta, Aniceto C. Jr.; Lagarto, Marites B.; Ortiz, Ma. Kristina P.; Ortiz, Danica Aisa P.; Potestad, Maropsil V. (Quezon City, Philippines Philippine Institute for Development Studies, 2019)
The enactment of Republic Act 10533 or the Enhanced Basic Education Act of 2013 added two years to basic education. One of the rationales offered by proponents of the law is that Senior High School (SHS) graduates will be equipped with skills and capacity to work or engage in entrepreneurial activities if they choose to do so. This study assesses the likelihood of achieving the employment and entrepreneurship objectives of the program by examining the experience of Grade 12 graduating students and the views of firms about the labor market prospects of the SHS graduates. It does this by (i) looking into the SHS curriculum and the competencies developed among the graduates, (ii) identifying the types of jobs that fit the Grade 12 graduates, (iii) gathering the private sector perspective on the jobs available and appropriate for the Grade 12 graduates, and (iv) providing policy recommendations for improving the implementation of the SHS program. The study revealed that despite identifying employment and entrepreneurship as a rationale for the program, three quarters of the Grade 12 students plan to proceed to higher education. This proportion is true even for those in the Technical- Vocational-Livelihood track. Among the highlights of the focus group discussion with students is the revelation that they are not very confident that they will get a job after graduating from SHS. Even those who passed the National Certification assessments still believe that the firms will prefer hiring college graduates over them. Meanwhile, most of the firms lack in-depth knowledge of the SHS program. They expressed the need to be exposed to the SHS graduates before they can be confident in hiring them. While it may be too early to gauge the performance of the SHS program, particularly the performance of its graduates in the labor market, the study has uncovered areas for improving the implementation of the program to boost the chances of achieving its objectives, particularly the employment and entrepreneurship capabilities of SHS graduates. --Back cover.
Includes bibliographical references (pages 97-99)
Keywords: High school graduates -- Employment -- Philippines; Labor supply -- Effect of education on -- Philippines; Education, Secondary -- Curricula -- Philippines